Post-Covid-19 Leadership Performance: A Proposed Study - Hikmah Perkasa, Didin; Purwanto, Setiyo; Lika Kabdiyono, Erna; Al Faruq Abdullah, Muhammad; Nina Rostina, Cut (KnE Social Sciences, 2023)
The progress of the organization is greatly influenced by the performance of employees. With the Covid-19 pandemic where companies have to change work system patterns and limit work time and processes to be able to survive in difficult times. This is important to do so that employee performance can be achieved as expected. Various literatures discuss a lot about the factors that affect employee performance. This research is important to do with the aim of knowing the influence of leadership style, workload and burnout on employee performance. The research method used in this study uses a quantitative causal approach with Likert scale measurements that are distributed to respondents through questionnaires. The role of the leader is one of the determining factors for the rise or fall of the performance of garment industry employees in Tangerang Regency. The workload felt by garment industry employees in Tangerang Regency makes employees complain about the workload being too heavy. With a high workload, employees feel physically and psychologically exhausted; therefore, employee performance is less than optimal. This research still has to be studied in depth and proven by data processing to find out how much influence leadership style, workload, and burnout have on the performance of garment industry production employees in Tangerang Regency and it is necessary to carry out a more detailed data analysis process to be able to produce optimal studies. Keywords: leadership style, workload, burnout, employee performance